Marine food production: problems and prospects for Latin America - May, Robert C. (Universidad de Costa Rica, 1978)
The present rate of fish consumption in Latin America is very low despite the existence of large fishery resources in the region. In view of the need for additionaI dietary protein which exists in many parts of Latin America, increasing the production and availability of fishery products should be given high priority in national and regional planning.